2014
DOI: 10.5935/abc.20140137
|View full text |Cite
|
Sign up to set email alerts
|

An Equation for the Prediction of Oxygen Consumption in a Brazilian Population

Abstract: BackgroundThe equations predicting maximal oxygen uptake (VO2max or peak) presently in use in cardiopulmonary exercise testing (CPET) softwares in Brazil have not been adequately validated. These equations are very important for the diagnostic capacity of this method.ObjectiveBuild and validate a Brazilian Equation (BE) for prediction of VO2peak in comparison to the equation cited by Jones (JE) and the Wasserman algorithm (WA).MethodsTreadmill evaluation was performed on 3119 individuals with CPET (breath by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
3
28
1
2
Order By: Relevance
“…Ten studies [29,[33][34][35][36][37][38][39][40][41] reported data for minute ventilation at peak exercise (VE peak ). Almost all studies reported VE peak data using tabulated data.…”
Section: Minute Ventilation At Peak Exercisementioning
confidence: 99%
“…Ten studies [29,[33][34][35][36][37][38][39][40][41] reported data for minute ventilation at peak exercise (VE peak ). Almost all studies reported VE peak data using tabulated data.…”
Section: Minute Ventilation At Peak Exercisementioning
confidence: 99%
“…The equation that had the greatest overestimate of the obese subjects CRF in this study was developed by Almeida et al . (Almeida et al ., ), with a mean difference of 36 ml min −1 kg −1 (Fig. d).…”
Section: Resultsmentioning
confidence: 89%
“…For cross-validation, the arithmetic mean between estimated and obtained VO 2 was calculated, and agreement analysis was performed using the Bland and Altman graphic method. We used the same method for comparing estimated and obtained peak VO 2 in three other equations previously developed (Hansen et al, 1984;Vivacqua & Hespanha, 1992;Almeida et al, 2014). Almeida et al recruited Brazilian subjects with a mean age of 42 years of both sexes.…”
Section: Methodsmentioning
confidence: 99%
“…According to another research 22 , when comparing predictive models with formulas already described in the literature, such as ACSM 7 or the formulas advocated by other authors 3 , it was shown that VO 2 could be accurately predicted using body mass index, age and workload as independent variables, when the volunteers are seemingly healthy and not athletes. In another study 23 , the authors developed an equation for the Brazilian population that takes into account the following variables: gender, age, BMI and physical activity level, comparing it with formulas used in the prediction of VO 2 , as that of previous studies 6,7,24 . The results indicated that both formulas overestimated the VO 2 when compared to the equation presented by them.…”
Section: Discussionmentioning
confidence: 99%